Validity and Effectiveness of Students Worksheet Based on Hands on Minds on Activities in Angiosperms Material to Train Argumentation Skill - Nurul Hikmah; Puspitawati Pratiwi Rinie (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2020)
Students worksheet is a learning media used to support learning process and develop cognitive abilities and students’ skills. Students worksheet was designed using hands on minds on approach to train argumentation skills in angiosperms material. This material asks students to group plants into divisio based on general charactertistics, link their role in daily life, and make phenetic and phylogenetic analysis. This research aimed to describe validity and effectiveness of student worksheet based on hands on minds on activity in angiosperm material to train argumentation skills. This student worksheet was developed with reference to planning, production, & evaluation (PPE) developmental model. This worksheet has limited trial test for 20 students in the class X SMAN 16 Surabaya. The data collection methods used were validation, questionnaire, and test. Data was analyzed descriptively and quantitatively. The result of this research showed that the validity of student worksheet based on experts validation was 97.75% with a very proper category. The effectiveness of students worksheet based on the result of students’ argumentation test had increased the pre-test to post-test from the quite good to be very good criteria, and the response of students was 93.67% with a very good category.